Ending cervical cancer: A call to action. (July 2017) - Aranda, Sanchia; Berkley, Seth; Cowal, Sally; Dybul, Mark; Evans, Tim; Iversen, Katja; Moeti, Matshidiso; Osotimehin, Babatunde; Peterson, Stefan; Piot, Peter; Purandare, Chittaranjan N.; Sidibé, Michel; et al.
Abstract: The outlook for elimination of the scourge of cervical cancer is bright, because we now have the tools to achieve this goal. In recent years human papillomavirus (HPV) vaccination in high‐income countries has resulted in dramatic decreases in HPV infection and associated cervical disease. If all countries with a substantial burden of disease introduce the vaccine nationally, we can protect the vast majority of women and girls most at risk. For women who are beyond the vaccination target age, progress has been made in screening and treatment for cervical precancer, but we must accelerate this momentum to reduce incidence and mortality worldwide to the very low rates found in wealthier countries. Human and financial resources must be increased and directed to programs that follow best practices and reach all women, including the marginalized or disadvantaged. Seven key actions are recommended. Now is the time for action at national, regional, and global levels. Abstract : Elimination of cervical cancer is now on the horizon if we rapidly scale up prevention in the low‐ and middle‐income countries that bear the highest burden of disease.